2021
DOI: 10.3389/fonc.2021.807410
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Immune Microenvironment Related Gene-Based Model to Predict Prognosis and Response to Compounds in Ovarian Cancer

Abstract: BackgroundThe tumor immune microenvironment (TIME) has been recognized to be an imperative factor facilitating the acquisition of many cancer-related hallmarks and is a critical target for targeted biological therapy. This research intended to construct a risk score model premised on TIME-associated genes for prediction of survival and identification of potential drugs for ovarian cancer (OC) patients.Methods and ResultsThe stromal and immune scores were computed utilizing the ESTIMATE algorithm in OC patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…There have been reports of various biological prognostic biomarkers for ovarian cancer [ 3 7 ]. Interestingly, Yang et al showed that some clinical variables were good predictors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of various biological prognostic biomarkers for ovarian cancer [ 3 7 ]. Interestingly, Yang et al showed that some clinical variables were good predictors [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the study screening gene pathways were very different, some of our constructed risk model genes were also screened as prognostic predictors of ovarian cancer in other ovarian cancer risk model studies, which further side validating the high accuracy of our constructed model: Fc Gamma Binding Protein (FCGBP) [18],Calcium Voltage-Gated Channel Subunit Alpha1 C (CACNA1C) [19],Ubiquitin D(UBD) [20,21],Peptidase Inhibitor 3(PI3) [22,23],Interferon Stimulated Exonuclease Gene 20 (ISG20) [24][25][26],A-Kinase Anchoring Protein 12(AKAP122) [26,27],Ribosomal Protein S6 Kinase A2(RPS6KA2)[28],C-X-C Motif Chemokine Ligand 11(CXCL11) [21,[29][30][31][32][33][34],Transient Receptor Potential Cation Channel Subfamily V Member 4(TRPV4) [35],Cholesterol 25-Hydroxylase(CH25H) [23,36],Solute Carrier Family 4 Member 8(SLC4A8) [37] However, the following genes have not been identi ed in ovarian cancer studies: Translocase Of Outer Mitochondrial Membrane 20 Like (TOMM20L), C-C Motif Chemokine Receptor 7(CCR7), Phosphatidylinositol Glycan Anchor Biosynthesis Class S(PIGS), Syntaxin 18(STX18), Carboxymethylenebutenolidase Homolog (CMBL)have not been found to be studied in ovarian cancer. This is the rst study to type ovarian cancer based on DDR-related genes and to investigate the prognostic relevance of genes that differ between types in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Via the “pRRophetic” package, we calculated the half-maximum inhibitory concentration (IC 50 ) to evaluate the difference in drug response between different groups in the Genomics of Drug Sensitivity in Cancer (GDSC) database ( 25 , 26 ) using Ridge’s regression, along with 10-fold cross-validation for the purpose of improving the accuracy of the prediction ( 27 , 28 ).…”
Section: Methodsmentioning
confidence: 99%